2019
DOI: 10.3389/fmars.2019.00013
|View full text |Cite
|
Sign up to set email alerts
|

Oceanography of Harmful Algal Blooms on the Ecuadorian Coast (1997–2017): Integrating Remote Sensing and Biological Data

Abstract: Borbor-Cordova et al. Harmful Algal Blooms on the Ecuadorian Coast produce toxins at high or at low concentrations. Considering that the Gulf of Guayaquil is essential to tourism, the shrimp industry, fisheries, and international shipping, these findings strongly suggest the need to establish an ecosystem health research program to monitor HABs and the development of a preventive policy for tourism and public health in Ecuador.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 94 publications
(102 reference statements)
2
6
1
Order By: Relevance
“…Interestingly, recent studies regarding phytoplankton distribution in response to ENSO events have been published , but, unfortunately, species identification is not indicated as a result. Another recent study explored the oceanography of red tides using remote sensing data from 1997 to 2017, confirmed that potential HABs have been dominated by dinoflagellates during wet season mostly at the Gulf of Guayaquil (Borbor-Cordova et al, 2019). Furthermore, dinoflagellates abundance reported in the present study was not high and the number of proliferations was low, only Gymnodinium sp exceeded 10 6 cell.…”
Section: Dinoflagellate Communitysupporting
confidence: 76%
See 2 more Smart Citations
“…Interestingly, recent studies regarding phytoplankton distribution in response to ENSO events have been published , but, unfortunately, species identification is not indicated as a result. Another recent study explored the oceanography of red tides using remote sensing data from 1997 to 2017, confirmed that potential HABs have been dominated by dinoflagellates during wet season mostly at the Gulf of Guayaquil (Borbor-Cordova et al, 2019). Furthermore, dinoflagellates abundance reported in the present study was not high and the number of proliferations was low, only Gymnodinium sp exceeded 10 6 cell.…”
Section: Dinoflagellate Communitysupporting
confidence: 76%
“…catenatum, P. micans, C. catenatum and Dinophysis caudata among others. As for the present study, lower abundances were registered for toxic species, slightly higher in the Gulf of Guayaquil than in La Libertad and Manta (Borbor-Cordova et al, 2019). Unfortunately, Esmeraldas was not considered in the study and data corresponded only to wet season.…”
Section: Dinoflagellate Communitycontrasting
confidence: 49%
See 1 more Smart Citation
“…Harmful algal blooms (HABs) have caused massive mortalities of bottlenose dolphins in Florida (e.g., Flewelling et al, 2005;Fire et al, 2015), as well as outbreaks of morbillivirus around the world (Taubenberger et al, 1996;Van Bressem et al, 2014). Red tides are not rare events in the Gulf of Guayaquil and some of them were confirmed to have been toxic (Borbor-Cordova et al, 2019), so it is not ruled out that a mortality event could have happened at that time. Outbreaks of mass cetacean mortality have not been reported in Ecuador but in the north of Peru in 2012 (200 km south the Gulf of Guayaquil) large-scale mortality involving more than 800 small cetaceans of six different species including bottlenose dolphins were reported (Instituto del Mar del Perú [IMARPE], 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This was done by using a gentle vacuum pump system as described in Boxhammer et al (2016). Small subsamples (in total < 10%) were used for particle sinking velocity and respiration measurements as described in Stange et al (2018). The bulk samples were concentrated by centrifugation, deep frozen at −30 • C and then freeze dried for 72 h. The dried bulk samples were ground in a ball mill to a homogeneous powder of 2 -60 µm particle size and analyzed for biogenic silica (BSi SED ), total particulate carbon (TPC SED ), nitrogen (TPN SED ), and phosphorus (TPP SED ) as described by Boxhammer et al (2016).…”
Section: Sediment Trap Sampling and Processingmentioning
confidence: 99%